Segurança Alimentar e Controle de Qualidade: um estudo da implantação do Programa Alimentos Seguros em supermercados de bairro - Guedes, Glenda Jamile Pires Barros (2008)
This study aimed to analyze the percentage of compliance, related to the requirements of Practice, achieved by 23 supermarkets in neighborhood after the deployment of Food Insurance Program. For its development research methodology adopted was the application start and end of a check-list (tool-specific SBP) in 23 supermarkets, target of this study. After the deployment of PAS was made a comparative study where it was possible to see that these companies need to improve conditions related to food safety, because according to the study, none of the 23 supermarkets evaluated met the criteria recommended by the SBP to 100% of compliance for the items critical of the check-list. Only 04 of the 23 supermarkets were in the range of 80 to 90% of the overall percentage of compliance, representing only 17.3% of the sample. Most of the sample submitted in a regular situation, according to the methodology of Cardoso (2001). Of the 23 supermarkets studied, 03 supermarkets were classified as poor (13.04%), 13 as scheduled (56.52%) as good and 07 (30.43%). You can see improvements in a small part of the sample, but the decline in the percentage of compliance of 02 companies after working for the implementation of the program, showing lack of responsibility and commitment of companies which should have as its top priority to food safety that market